Combining the effects of increased atmospheric carbon dioxide on protein, iron, and zinc availability and projected climate change on global diets: a modelling study - Beach, Robert H.; Sulser, Timothy B.; Crimmins, Allison; Cenacchi, Nicola; Cole, Jefferson; Fukagawa, Naomi K; Mason-D'Croz, Daniel; Myers, Samuel; Sarofim, Marcus C; Smith, Matthew R.; Ziska, Lewis H. (Elsevier, 2019)
Despite substantial decreases in the rate of global undernutrition over the past few decades, a large global burden of disease associated with deficits in intake of protein, iron, zinc, and other nutrients remains. Additionally, progress in decreasing undernutrition has stagnated or deteriorated in many countries.1 25–30% of the global population are deficient in at least one key micronutrient. This proportion includes an estimated 10–15% of people who are at risk of insufficient iron intake, 17% at risk of zinc deficiency, and 12% at risk of protein deficiency. Increasing population and nutrient demands and the effects of climate change have the potential to exacerbate these threats to global food security. Chronic dietary deficiencies of micronutrients contribute to so-called hidden hunger, for which the consequences (eg, adverse effects on metabolism, the immune system, cognitive development, and maturation) might not be immediately visible or easily observed. Children and pregnant women are especially vulnerable to nutritional deficits. Insufficient protein intake, which might coincide with micronutrient deficiencies, restricts growth and tissue repair and results in low birthweight, wasting, stunting, and other health issues that cause approximately 2·2 million annual deaths in children younger than 5 years. Zinc deficiency is estimated to cause approximately 100 000 deaths per year in children younger than 5 years. The global burden of disease associated with iron deficiency has been estimated at nearly 200 000 deaths and 45 million disability-adjusted life-years annually.